Characteristics of Cerebral Hemodynamics and Vascular Responsiveness of Brain Arteries among HIV-Infected Patients - Satima R. Kuranbaeva1, Gulnara Rakhimbaeva2, S.H. Kalandarova3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The damage features of the cerebral hemodynamics disorders and decreased responsiveness of brainvessels among the patients with HIV are the pathogenetic basis for the formation of HIV encephalopathydevelopment. We observed patterns of changes in cerebral blood flow and immunological reactivity amongpatients at preclinical stages of HIV. It indicates that the vascular system of the brain is highly sensitive tothe action of treponemous toxin and is responsive to damages at the early stages of the disease.